Childhood Maltreatment Alters the Neural Processing of Chemosensory Stress Signals - Maier, Ayline; Heinen-Ludwig, Luca; Güntürkün, Onur; Hurlemann, René; Scheele, Dirk (Frontiers in Psychiatry, 2020)
Accumulating evidence suggests that childhood maltreatment (CM) confers risk for psychopathology later in life by inducing hypervigilance to social threat cues such as fearful faces. However, it remains unclear whether the modulatory impact of CM extents to the olfactory domain of social communication in humans. To address this question, we examined whether CM modulates the neural processing of chemosensory threat signals in sweat and whether CM affects the stress-reducing effects of oxytocin (OXT) in this context. In a randomized, double-blind within-subject functional MRI study design, 58 healthy participants (30 females) received intranasal OXT (40 IU) or placebo (PLC) and completed a forced-choice emotion recognition task with faces of varying emotion intensities (neutral to fearful) while exposed to sweat stimuli and a non-social control odor. Axillary sweat samples were collected from 30 healthy male donors undergoing an acute psychosocial stressor (stress) and ergometer training (sport) as control in a pre-study. CM was assessed by the 25-item Childhood Trauma Questionnaire (CTQ). The final fMRI analysis included 50 healthy participants (26 females). Regression analysis showed a stress-specific association of CTQ scores with amygdala hyperreactivity, hippocampal deactivation and increased functional connectivity between the amygdala and the hippocampus, medial orbitofrontal cortex and the anterior cingulate cortex (ACC) under PLC. Furthermore, we observed a positive association of CTQ scores and the dampening effects of OXT on stress-related amygdala responses. Our findings suggest that CM may induce hypervigilance to chemosensory threat cues in a healthy sample due to inefficient frontolimbic inhibition of amygdala activation. Future studies should investigate whether increased recruitment of the intralimbic amygdala-hippocampus complex reflects a compensatory mechanism that prevents the development of psychopathology in those who have experienced CM. Furthermore, the results reveal that the stress-specific effects of OXT in the olfactory domain are more pronounced in participants with increasing levels of CM exposure.